Unveiling the Relationship Between Sea Surface Hydrographic Patterns and Tuna Larval Distribution in the Central Mediterranean Sea - Russo, Stefania; Torri, Marco; Patti, Bernardo; Reglero, Patricia; Álvarez-Berastegui, Diego; Cuttitta, Angela; Sarà, Gianluca (Frontiers in Marine Science, 2021)
Thunnus thynnus (Atlantic bluefin tuna, ABT) and other tuna species reproduce in the Mediterranean Sea during the summer period. Despite the Central Mediterranean Sea, the Strait of Sicily in particular, being a key spawning site for many tuna species, little is known on the effects of oceanographic variability on their larval distribution in this area. The abundance and presence-absence of larval specimens for three tuna species (ABT, bullet tuna and albacore) were modeled in order to examine their relationships with environmental factors, by analysing historical in situ information collected during seven annual surveys (2010–2016). The results revealed that most tuna larvae for the three species were found in the easternmost part of the study area, south of Capo Passero. This area is characterized by a stable saline front and warmer nutrient-poor water, and it has different environmental conditions, compared with the surrounding areas. The models used to investigate the presence-absence and abundance of the three species showed that ABT was the most abundant, followed by bullet tuna and albacore. The presence and abundance data collected are comparable with those of other spawning areas in the Mediterranean. Regarding biological and physical parameters, the results suggest that temperature, salinity, and day of the year are the key factors for understanding the ecological mechanisms and geographical distribution of these species in this area. Temperature affects the presence of ABT larvae and salinity, which, with a physical barrier effect, is a key factor for the presence-absence of bullet and albacore and for albacore abundance.